Optimized 5G-IoT Probe: Hardware Innovations and Practical Deployment - Paluřík, Pavel; Dvořák, Radim; Mašek, Pavel (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
The efficient deployment of 5G-IoT networks relies on accurate field measurements to evaluate network performance in diverse environments. This study introduces a newly optimized 5G-IoT tester, developed to enhance the accuracy and efficiency of LTE-M and NB-IoT coverage assessment. The redesigned hardware and software architecture provide improved power efficiency, enhanced configurability, and intuitive user controls, making it a robust tool for industrial applications and network planning. Initial field measurements were conducted as part of a large-scale data collection effort, covering a subset of predefined 1,000 test locations. The recorded data were analyzed through heatmap visualizations, revealing coverage disparities, particularly in peripheral regions, and emphasizing the need for targeted network optimizations. Future work aims to expand the dataset, enabling more comprehensive coverage analysis and validation of predictive models for IoT deployment.
Keywords: 5G-IoT; LTE-M; NB-IoT; signal analysis; network performance; field measurements; IoT connectivity